Breeding the Best and the Brightest: A Legal Viewpoint - Lee, Mei Pheng (Journal of Malaysian and Comparative Law, 1984)
Singapore is well-known as a very population-conscious city-state. Indeed, its comprehensive population control programme is an outstanding achievement. Many population control concepts, which will be discussed later, have been adopted in Singapore. However, none of these provoked as much controversy and indignation in the country and abroad as when Prime Minister Lee Kuan Yew, in his August 14, 1983 National Day address, made the first announcement designed to encourage women graduates to reproduce or to reproduce more. Prime Minister Lee stated to the effect that because women-graduates do not reproduce enough or do not even get married, they are wasting talent-laden genes in the cause of population control. He reasoned that due to this factor some four hundred graduates were being lost annually.